Differential response of tissue engineered skeletal muscle from rheumatoid arthritis patients and healthy controls - Catherine E. Oliver; Jonathan L. Carter; James S. Hong; Mingzhi Xu; William E. Kraus; Kim M. Huffman; George A. Truskey (Communications Biology)
Abstract Rheumatoid arthritis (RA) is a chronic inflammatory disease affecting articular joints and skeletal muscle. To assess the role of cytokines upon muscle strength in RA, we developed an in vitro tissue-engineered human skeletal muscle model (myobundle). Myobundles were generated using primary skeletal muscle cells from the vastus lateralis muscle of RA patients and age-matched healthy controls. RA myobundles were more sensitive to 5 ng/mL IFN-γ, exhibiting reduced contractile force and altered contraction kinetics. Addition of IL-6 with or without IFN-γ led to a small but significant increase in striated fibers. Gene sets involved in the response to hypoxia, MTOR1 signaling, and the unfolded protein response were enriched in IFN-γ-treated RA myobundles, but not IFN-γ-treated controls. Tofacitinib increased contractile force and myosin heavy chain levels and restored PIM1 protein levels in RA myobundles treated with IFN-γ. Thus, in RA muscle, low levels of IFN-γ selectively increase gene pathways that reduce contractile force.